Analysis on the different targets and bi-static angles to the radar cross section using LTE frequency / Muhammad Haziq Hazwan Md Yunos - Md Yunos, Muhammad Haziq Hazwan (2014)
This paper presents on the analysis of the effect of different targets and bi-static angles to the radar cross section (RCS) using Long Term Evolution (LTE) frequency. The targets used in this project are Toyota Rush and Proton Exora. The modelings of cars are designed using Autodesk 3Ds Max and then export to CST Microwave Studio in order to simulate the radar cross section. Analyses of simulation of a target with different bi-static angles and different cars in backscatter radar are conducted for 59 and 90 degree plane wave propagation. Dimensions used for designing the car are based on the actual car whereas the material used for the car is perfect electrical conductor (PEC). It is observed that the readings of RCS are different depends on the shape and size of car. The different angles of plane wave give different readings of RCS.